Long-term air pollution and adverse meteorological factors might elevate the osteoporosis risk among adult Chinese - Sun, Hong; Wan, Yanan; Pan, Xiaoqun; You, Wanxi; Shen, Jianxin; Lu, Junhua; Zheng, Gangfeng; Li, Xinlin; Xing, Xiaoxi; Zhang, Yongqing (Frontiers in Public Health, 2024)
Objective This study aims to investigate the relationship between exposure to air pollution and adverse meteorological factors, and the risk of osteoporosis. Methods We diagnosed osteoporosis by assessing bone mineral density through Dual-Energy X-ray absorptiometry in 2,361 participants from Jiangsu, China. Additionally, we conducted physical examinations, blood tests, and questionnaires. We evaluated pollution exposure levels using grid data, considering various lag periods (ranging from one to five years) based on participants’ addresses. We utilized logistic regression analysis, adjusted for temperature, humidity, and individual factors, to examine the connections between osteoporosis and seven air pollutants: PM₁, PM₂.₅, PM₁₀, SO₂, NO₂, CO, and O₃. We assessed the robustness of our study through two-pollutant models and distributed lag non-linear models (DLNM) and explored susceptibility using stratified analyses. Results In Jiangsu, China, the prevalence of osteoporosis among individuals aged 40 and above was found to be 15.1%. A consistent association was observed between osteoporosis and the five-year average exposure to most pollutants, including PM₂.₅, PM₁₀, CO, and O₃. The effects of PM₁₀ and CO remained stable even after adjusting for the presence of a second pollutant. However, the levels of PM₁ and PM₂.₅ were significantly influenced by O₃ levels. Individuals aged 60 and above, those with a BMI of 25 or higher, and males were found to be more susceptible to the effects of air pollution. Interestingly, males showed a significantly higher susceptibility to PM₁ and PM₂.₅ compared to females. This study provides valuable insights into the long-term effects of air pollution on osteoporosis risk among the adult population in China. Conclusion This study indicates a potential association between air pollutants and osteoporosis, particularly with long-term exposure. The risk of osteoporosis induced by air pollution is found to be higher in individuals aged 60 and above, those with a BMI greater than 25, and males. These findings underscore the need for further research and public health interventions to mitigate the impact of air pollution on bone health.